Authors' reply - Diener, Markus K.; Knebel, Phillip; Kieser, Meinhard; Probst, Pascal; Büchler, Markus W. (The lancet, 2014)
We thank Tetsuji Fujita for his very insightful comments about our PROUD trial.1 We - followed his suggestion to look further into subgroups of all the patients in our - trial, which then were comparable with the trial groups of the single-centre studies - by Nakamura and colleagues,2 Justinger and colleagues,3 and the multicentre trial - by Galal and El-Hindawy.4 Results from these trials showed, in contrast with our PROUD - trial,1 a significantly reduced rate of surgical site infections (SSI) using triclosan-coated - sutures.
Gesehen am 06.07.2020